Step-by-step explanation:
7. Ans;
\frac{6 {a}^{5} {b}^{7} }{ - 2 {a}^{3} {b}^{7} } = \frac{2 {a}^{3} {b}^{7}(3 {a}^{2} ) }{ - 2 {a}^{3} {b}^{7} } = - 3 {a}^{2}
−2a
3
b
7
6a
5
b
7
=
−2a
3
b
7
2a
3
b
7
(3a
2
)
=−3a
2
___o____o___
8. Ans;
\frac{ - 20 {x}^{3} {y}^{2} }{ - 5 {x}^{3}y } = \frac{ - 5 {x}^{3}y(4y) }{ - 5 {x}^{3}y } = 4y
−5x
3
y
−20x
3
y
2
=
−5x
3
y
−5x
3
y(4y)
=4y
___o___o___
9. Ans;
\frac{ - 16 a {b}^{4} }{4 {b}^{3} } = \frac{4 {b}^{3}( - 4ab) }{4 {b}^{3} } = - 4ab
4b
3
−16ab
4
=
4b
3
4b
3
(−4ab)
=−4ab
____o____o____
10. Ans;
\frac{21 {m}^{8} {n}^{5} }{27 {m}^{5} {n}^{4} } = \frac{3 {m}^{5} {n}^{4}(7 {m}^{3} n) }{3 {m}^{5} {n}^{4}(9) } = \frac{7 {m}^{3}n }{9}
27m
5
n
4
21m
8
n
5
=
3m
5
n
4
(9)
3m
5
n
4
(7m
3
n)
=
9
7m
3
n
___o___o___
11. Ans;
\frac{ - 15 {x}^{5} {y}^{4} }{45x {y}^{3} } = \frac{ 15x {y}^{3} ( - {x}^{4} y)}{15x {y}^{3}(3) } = - \frac{ {x}^{4}y }{3}
45xy
3
−15x
5
y
4
=
15xy
3
(3)
15xy
3
(−x
4
y)
=−
3
x
4
y
___o___o___
12.Ans;
\frac{7 {p}^{2} {q}^{2} }{14 {p}^{2} {q}^{2} } = \frac{7 {p}^{2} {q}^{2} }{7 {p}^{2} {q}^{2} (2) } = \frac{1}{2} = 0.5
14p
2
q
2
7p
2
q
2
=
7p
2
q
2
(2)
7p
2
q
2
=
2
1
=0.5